European Union law : text and materials - Chalmers, Damian; Davies, Gareth; Monti, Giorgio (Cambridge : Cambridge University Press, 2019)
As the preferred choice on EU law for both teachers and students, this textbook offers an unrivalled combination of expertise, accessibility and comprehensive coverage. Written in a way which combines clarity with sophisticated analysis, it stimulates students to engage fully with the sometimes complex material, and encourages critical reflection. The new edition reflects the challenges facing the European Union now, with dedicated chapters on Brexit, the migration crisis and the euro area, and with further Brexit materials and analysis integrated wherever relevant. Materials from case law, legislation and academic literature are integrated throughout to present the student with the broadest range of views and deepen understanding of the context of the law. A dedicated site introduces students to the wide ranging debates found in blogs on EU law, EU affairs more generally and Brexit. This is a required text for all interested in European Union law.
European integration and the treaty on European union -- The EU institutions -- Union law-making -- The EU judicial order -- The authority of EU law -- Fundamental rights -- Rights and remedies in national courts -- Infringement proceedings -- Judicial review -- Brexit -- EU citizenship -- EU law and non-EU nationals -- Equal opportunities law -- The internal market -- Economic and monetary union -- Free movement of goods -- Free movement of services -- The pursuit of an occupation in another member state -- Trade restrictions and public goods -- EU competition law : function and enforcement -- Antitrust and monopolies -- State aids.
Title from publisher's bibliographic system (viewed on 04 Dec 2019).
Keywords: elektronické knihy; electronic books; European Union; Law -- European Union countries